Are There Static-Structural Biomarkers for Glaucoma with OCT? Gibt es statisch-strukturelle Biomarker bei den Glaukomen mit der OCT? - Mardin, Christian (Klinische Monatsblätter für Augenheilkunde, 2022)
Glaucomas lead to uniform, specific and slowly developing atrophy of the optic nerve with progressing visual field defects in late stages. Early diagnosis is challenging, but necessary as optic nerve damage is irreparable. Biomarkers with structural optical coherence tomography (OCT) flag optic atrophy but do not prove to be specific in the differential diagnosis to other forms of optic atrophy. Combination of OCT parameters and their correlation to other variables facilitate glaucoma diagnosis. Use of artificial intelligence (AI) in structural OCT images may prove to be superior and as biomarker more specific to thickness measurements of neuronal tissues alone.
CRIS-Team Scopus Importer:2022-03-11